The Form and Function of Local Language in Directive Speech Act at A University in Central Sulawesi - kundharu saddhono; Fatma Kasim (Bina Nusantara University, 2016)
The aim of this research was to describe the local language form, function, and typical of it in the directive act at the university in Central Sulawesi. The method used in this research was descriptive qualitative in socio-pragmatics approach. The source of the data was gained from lecturers and students utterances in discourse lecture. The data collection used note taking. Meanwhile, the techniques of analyzing data were the interactive analysis that consisted of four steps, namely data collection, data reduction, data analysis, and verification or drawing the conclusion. The result of the research shows that the local language form in directive act consisted of imperative, interrogative, and declarative. The functions of local language in directive acts are the prohibitive function, suggestive function, requestive, and permissive function. The typical local language that used is characterized by regional language and its dialect.